2002
DOI: 10.1071/mf02082
|View full text |Cite
|
Sign up to set email alerts
|

Fate of juvenile school prawns, Metapenaeus macleayi, after simulated capture and escape from trawls

Abstract: Two laboratory experiments were done to assess the fate of juvenile school prawns, Metapenaeus macleayi, after simulated multiple capture and escape from trawls. In the first experiment, prawns that were trawled and escaped one, five or 10 times, sustained some physical damage (mostly limited to the loss of antennae), but this was not significantly different from that sustained by control prawns that had not been trawled. Similarly, there were no significant differences between the different treatments and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 19 publications
1
33
1
Order By: Relevance
“…Mean L-lactate concentrations (± SE) ranged between 0.5 ± 0.21 and 2.22 ± 0.38 µmol g-1 (Fig. 5) and approached baseline levels (3.72 ± 0.38 µmol g-1 ) previously recorded for this species (e.g., Broadhurst et al 2002). Such low levels of the metabolite in active school prawns indicate that they were not overly stressed during the experimental procedure.…”
Section: Prawns Used In Experimentsmentioning
confidence: 71%
See 4 more Smart Citations
“…Mean L-lactate concentrations (± SE) ranged between 0.5 ± 0.21 and 2.22 ± 0.38 µmol g-1 (Fig. 5) and approached baseline levels (3.72 ± 0.38 µmol g-1 ) previously recorded for this species (e.g., Broadhurst et al 2002). Such low levels of the metabolite in active school prawns indicate that they were not overly stressed during the experimental procedure.…”
Section: Prawns Used In Experimentsmentioning
confidence: 71%
“…Although the fate of school prawns escaping from recreational gears was not examined here, a previous study by Broadhurst et al (2002) demonstrated minimal stress, physical damage and mortality (<11% over 2 weeks post-escape) by the same size cohort after their simulated multiple capture and escape from trawls. During this earlier work, the mean L-lactate concentration recorded from school prawns at 2 min post-escape (7.78 ± 0.5 µmol g-1 ) was considerably greater than that observed here (e.g., between 0.58 ± 0.22 and 1.63 ± 0.61 µmol g-1 - Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations